2014
DOI: 10.5603/cj.a2013.0116
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of chronic kidney disease as predictor of atrial fibrillation recurrence following catheter ablation

Abstract: (Cardiol J 2014; 21, 1: 89-95)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
5
24
0
4
Order By: Relevance
“…In 3 studies, kidney dysfunction was an independent predictor of AF recurrence upon ECG or Holter recordings conducted at 3‐month intervals . A meta‐analysis combining these data reported a significant association between an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73m 2 and AF recurrence with at least 1 year of follow‐up (pooled HR: 2.32, 95%CI: 1.61–3.35, P < 0.001) . Another study examining 702 ablation recipients reported an association between CKD and AF recurrence using a cutpoint of eGFR <68 mL/min/1.73m 2 (HR: 1.43, 95%CI: 1.05–1.95, P = 0.007) .…”
Section: Discussionmentioning
confidence: 99%
“…In 3 studies, kidney dysfunction was an independent predictor of AF recurrence upon ECG or Holter recordings conducted at 3‐month intervals . A meta‐analysis combining these data reported a significant association between an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73m 2 and AF recurrence with at least 1 year of follow‐up (pooled HR: 2.32, 95%CI: 1.61–3.35, P < 0.001) . Another study examining 702 ablation recipients reported an association between CKD and AF recurrence using a cutpoint of eGFR <68 mL/min/1.73m 2 (HR: 1.43, 95%CI: 1.05–1.95, P = 0.007) .…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the P wave during sinus rhythm preceding the new-onset AF episode, 101 patients who had sinus rhythm ECG recordings within 12 months before the new-onset AF episode were selected. In addition, to enable the evaluation of cardiac Vol 55 No 5 PREDICTION OF NEW-ONSET AF VIA P WAVE ANALYSIS structural changes at this point in each patient, 68 patients who had echocardiographic recordings within 12 months before the AF episode were selected as the study population ( Figure 1). As the control population, 332 patients without AF episodes who had ECG recordings in the same period of this study were randomly selected from the digital ECG profiling system of Kitasato University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Even when considering catheter ablation for AF, it is important to detect the early or precursor state of AF in clinical cases because the effect of catheter ablation is higher in patients with earlier-stage AF, even in those with simple circumference ablation of pulmonary veins. [5][6][7] The arrhythmogenic substrate of AF is known to be constructed progressively under various pathological conditions, including AF itself; [7][8][9][10][11] therefore, it could be speculated that the electrophysiological properties of the atrium may be modified in its precursor state. Several studies have attempted to identify the changes in P waves during sinus rhythm in AF patients.…”
mentioning
confidence: 99%
“…There is also a wide spectrum of patients with CKD, and whether patients with more advanced CKD got AF ablation is not clear. Systematic reviews and other studies have suggested higher recurrence after AF ablations in patients with CKD . The authors do look at important endpoints such as repeat procedures, cardioversions, or hospitalizations; however, we have to accept that recurrence of AF by monitoring in this study cannot be assessed, which is a major flaw.…”
Section: Is Af Ablation the Same In Patients With Ckd?mentioning
confidence: 98%